Implementasi Nilai Karakter Religius Melalui Program Tahfidz Al-Qur’an di SMPN 2 Bandar Lampung - Arrozi, Fahrudin; Syafe'i, Imam; Abbas, Erjati (CV. Creative Tugu Pena, 2024)
Character education will grow well if it starts from instilling a religious spirit in students. Therefore, an effective way to instill religious character values in students is through the process of memorizing the Koran, students not only learn by rote but also deepen Islamic teachings which contain various moral and ethical values as a developer of love for al-Qur'an. al-Qur'an as a guide to life. Apart from that, success in implementing religious character values in schools is also determined by the application of appropriate learning strategies and methods. Strategies and methods in learning, in the tahfidz al-Qur'an program that researchers carry out. The effort to improve the Islamic personality of students is to prepare students to believe, appreciate and practice the teachings of the Islamic religion. This research is included in qualitative field research (filed research). SMP Negeri 2 Bandar Lampung as a data source for the research study conducted. Data collection methods use interviews, observation and documentation. The data analysis used is a qualitative descriptive approach. The religious character values that are instilled include discipline, cleanliness, hard work, honesty, sincerity, patience, trustworthiness and responsibility which are applied through exemplary methods, habituation, advice and the Reward and Punishment Method.